Septins tune lipid kinase activity and PI(4,5)P2 turnover during G-protein-coupled PLC signalling in vivo. - Kumari, A.; Ghosh, A.; Kolay, S.; Raghu, P. (Life science alliance, 2022)
Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] hydrolysis by phospholipase C (PLC) is a conserved mechanism of signalling. Given the low abundance of PI(4,5)P2, its hydrolysis needs to be coupled to resynthesis to ensure continued PLC activity; however, the mechanism by which depletion is coupled to resynthesis remains unknown. PI(4,5)P2 synthesis is catalyzed by the phosphorylation of phosphatidylinositol 4 phosphate (PI4P) by phosphatidylinositol 4 phosphate 5 kinase (PIP5K). In Drosophila photoreceptors, photon absorption is transduced into PLC activity and during this process, PI(4,5)P2 is resynthesized by a PIP5K. However, the mechanism by which PIP5K activity is coupled to PI(4,5)P2 hydrolysis is unknown. In this study, we identify a unique isoform dPIP5KL, that is both necessary and sufficient to mediate PI(4,5)P2 synthesis during phototransduction. Depletion of PNUT, a non-redundant subunit of the septin family, enhances dPIP5KL activity in vitro and PI(4,5)P2 resynthesis in vivo; co-depletion of dPIP5KL reverses the enhanced rate of PI(4,5)P2 resynthesis in vivo. Thus, our work defines a septin-mediated mechanism through which PIP5K activity is coupled to PLC-mediated PI(4,5)P2 hydrolysis.